DAMPAK PENERAPAN METODE KULIAH TUJUH MENIT TERHADAP KEPERCAYAAAN DIRI BERBICARA DI DEPAN UMUM PADA SISWA MAN 1 BUTON SELATAN - Muzainah; Ramly; Candra Dewi, Anita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Impact of the Implementation of the Seven-Minute Lecture Method on Public Speaking Confidence of Students at MAN 1 Buton Selatan. This study aims to determine the impact of the implementation of the sevenminute lecture method (kultum) on public speaking confidence among students of MAN 1 South Buton. This study uses a quantitative approach with an ex post facto research type. The study population was all students of MAN 1 South Buton, with a sample of 81 students selected using a purposive sampling technique. Data collection was carried out through questionnaires, while data analysis used simple linear regression analysis. The results of the study indicate that the application of the seven-minute lecture method (kultum) has a positive and significant impact on students' public speaking confidence, as evidenced by the significance value (Sig.) In addition, the analysis of the determination coefficient results showed that the seven-minute lecture method contributed 60.3% to public speaking confidence, while the rest was influenced by other factors outside this study. Based on the results of the study, it can be concluded that the seven-minute lecture method can be used as an effective practice-based learning method in increasing public speaking confidence in students of MAN 1 South Buton.